Child and adolescent COVID-19 vaccination status and reasons for non-vaccination by parental vaccination status. (August 2022) - Nguyen, K.H.; Nguyen, K.; Mansfield, K.; Allen, J.D.; Corlin, L.
Abstract: Objectives: COVID-19 vaccines are recommended for children ages ≥5 years. To develop effective interventions to increase uptake, this study explores reasons for parental hesitancy of child and adolescent COVID-19 vaccination. Study design: The Household Pulse Survey (HPS) is a nationally representative cross-sectional online household survey of adults aged ≥18 years that began data collection in April 2020 to help understand household experiences during the COVID-19 pandemic. Methods: Using data from December 29, 2021, to January 10, 2022 ( n = 11, 478), we assessed child and adolescent COVID-19 vaccination coverage and parental intent to vaccinate their children and adolescents. Factors associated with child and adolescent vaccination coverage were examined using multivariable regression models. Reasons for not having had their child or adolescent vaccinated, stratified by parental vaccination status, were compared using tests of differences in proportions. Results: Less than one-half (42.3%) of children and three-quarters (74.8%) of adolescents are vaccinated. Vaccination coverage was lower among households with lower education, as well as among children who had not had a preventive check-up in the past year. Parents of unvaccinated children were more likely to report that they do not trust COVID-19 vaccines, do not trust the government, and do not believe children need a COVID-19 vaccine compared to parents of vaccinated children. Conclusion: Efforts to increase uptake of vaccines by children and adolescents should target those with lower education, reassure parents of the vaccine safety and efficacy for themselves and their children/adolescents, and support yearly preventive care visits for their children.